2019
DOI: 10.1590/s0102-865020190010000004
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole concentration in the bloodstream following its topical application, at different concentration levels, on experimental skin wounds during healing by secondary intention

Abstract: Purpose To characterize qualitatively and quantitatively the absorption of metronidazole solution, in greater concentrations and for longer periods, when applied topically to an experimental open skin wound model. Methods An open skin wound, 2 cm in diameter and total skin thickness was prepared, under anesthetic, in the dorsal region of 108 Wistar rats weighing between 300 and 350 grams. The animals were allocated to groups of 18 animals in accordance with the concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, these mechanisms apply only to the high serum levels achieved after intravenous or oral dosing. Sampaio CPP et al showed that in experimental rats, the serum concentration of metronidazole following topical application to a skin wound was between 0.001% and 0.002% and was uninfluenced by the concentration, duration and surface area (wound extent) on which TM was applied [ 25 ]. This characterizes an extremely low level of metronidazole in the bloodstream following topical application and does not appear to be responsible for the increased hemorrhagic risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, these mechanisms apply only to the high serum levels achieved after intravenous or oral dosing. Sampaio CPP et al showed that in experimental rats, the serum concentration of metronidazole following topical application to a skin wound was between 0.001% and 0.002% and was uninfluenced by the concentration, duration and surface area (wound extent) on which TM was applied [ 25 ]. This characterizes an extremely low level of metronidazole in the bloodstream following topical application and does not appear to be responsible for the increased hemorrhagic risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, multiple methods have been described for analyzing MTZ in different biological matrices and with a wide application of HPLC. The quantification of MTZ using HPLC has been described for different matrices: human whole blood samples (Fonnes et al, 2020); subcutaneous plasma and microdialysate from humans (Dorn et al, 2019); plasma and bile fluid from humans (Yoon et al, 2020); muscle tissue, plasma, and microdialysate from humans (Karjagin et al, 2004); rat plasma (Sampaio et al, 2019); and blood, brain, and biliary microdialysate from rats (Tsai & Chen, 2003), in addition to human feces (Jeffery et al, 2017). However, there are no reports of the analytical method using HPLC to determine MTZ in peritoneal microdialysate and compare it with blood microdialysate from rats.…”
Section: Introductionmentioning
confidence: 99%